ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PADA PT. MAHAKA MEDIA TBK - Hardinata, Denny (Universitas Widya Kartika Surabaya, 2024)
In Indonesia, many business entities choose to make acquisitions. However, in reality, the acquisition is not certain to provide good results for both business entities. There have been many examples of cases of business entities experiencing losses after making acquisitions. The aim of this research is to find out whether there are differences in financial performance at PT. Mahaka Media Tbk before and after acquiring PT. Gamma Investa Lestari uses liquidity ratios, solvency ratios, profitability ratios and activity ratios. The type of research in this research is comparative, with the population being business entities that made acquisitions in 2017. The sample collection method used purposive sampling, so that a sample of PT business entities was obtained. Mahaka Media Tbk which acquired PT. Gamma Investa Lestari on June 19 2017. The analysis method used is the paired sample t-test. Based on the results of the analysis using the paired sample t-test, only the activity ratio had differences before and after the acquisition, while for the liquidity ratio, solvency ratio and profitability ratio there were no differences.